The Heterogeneity of Growth Mindset and Academic Grit Among Chinese Adolescents - Lin, Rong‐Mao; Lin, Yan; Yu, Qiao‐Hua; Liao, Hong‐Yu (Psychology in the schools, 2025)
ABSTRACT Growth mindset and academic grit are crucial for adolescents’ academic achievement. However, previous research that explored their relationship through variable‐centered approaches cannot adequately address the group heterogeneity. This study addressed the issue by conducting latent profile analysis and social network analysis with a sample of 1171 Chinese adolescents, examining the different subgroups of the adolescents in terms of growth mindset and academic grit, and the distinct core characteristics of these subgroups. Latent profile analysis revealed four heterogeneous subgroups: (1) Fixed Vulnerability: (C1, 15.0%) with believing in difficulty changing intelligence and lack of grit; (2) Composite: (C2, 17.3%) with believing in difficulty changing intelligence but having strong grit; (3) Growth Grit: (C3, 22.1%) with believing in intelligence improvement through effort and having robust grit; and (4) Intermediate: (C4, 40.9%) with believing in intelligence improvement through effort and having moderate grit. Regression mixture modeling showed that older adolescents were more likely to fall into the Fixed Vulnerability subgroup. Social network analysis showed that subgroups C1 and C4 emphasized growth mindset, while C2 and C3 highlighted academic grit. The study indicates the heterogeneity in growth mindset and academic grit among Chinese adolescents, suggesting the need for educational practitioners to apply more targeted intervention measures for various subgroups. Summary Chinese adolescents exhibit heterogeneity with four subgroups in terms of growth mindset and academic grit. The four subgroups exhibit different network structure and core features of each subgroup. Older adolescents were more likely to fall into the Fixed Vulnerability subgroup.